Trikora: A Case Study from Diplomacy to Military Campaign - Benny Octaviar; Almuchalif Suryo; Syaiful Anwar (Budapest International Research and Critics University, 2022)
The war between Indonesia and the Netherlands led to the Round Table Conference (KMB) negotiationsin The Hague in 1949 with the main result being the formal recognition by the Netherlands of Indonesian sovereignty on 27 December 1949. One of the points of the KMB agreement stipulates that the West Irian issue will be resolved within a year. But in reality the Netherlands did not keep its promise. The effort to return West Irian back to Indonesia is a big agenda. To find out these efforts, historical research was carried out using the steps of descriptive qualitative research methods with data collection techniques using library research. The results of the study found that the Government of Indonesia in its efforts to restore West Irian had gone through three stages as follows: The first stage was through the bilateral negotiation table between Indonesia and the Netherlands. The second stage is through international mediation and the third stage is by way of confrontation or military campaign. This effort finally succeeded in forcing the Netherlands to return to negotiations to settle the West Irian issue and sign the 1962 New York Agreement.